أهمية الضريبة على الدخل الإجمالي في حصيلة الإيرادات الجبائية العادية في الجزائر (2020- مديرية الضرائب لولاية الشلف نموذجا ( 20: The importance of the tax on gross income in the proceeds of ordinary tax revenues in Algeria-Tax Directorate of the Wilaya of Chlef as a model (2014-2020) - حدو محمد; البكاي الهادي (Journal of North African Economies, 2025)
This study aims to determine the percentage of the contribution of the tax on gross income to the proceeds of ordinary tax revenues compared to other types of taxes. The total income in the proceeds of ordinary tax revenues is the highest, as it was estimated during the study period (2014-2020) on average at the level of 60.77%, while the contribution rate of the fee on professional activity, the fee on value-added, registration rights and stamp was at the level of 10.41%, 9.99 % and 9.03%, respectively.